KEPUTUSAN MAJELIS ULAMA INDONESIA TENTANG PEMIMPIN YANG DIPILIH - Rastana Dermayu; Adang Djumhur Salikin; Wasman Wasman (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2020)
Â ABSTRACTThe decision of the Indonesian Ulema Council in 2009 in accordance with Law number 39 of 1999 concerning human rights article 43 and Law number 12 of 2005 concerning Ratification of the Covenant on Civil Civil Rights Article 25. In this case the MUI is moderate. The decision of the Indonesian Ulema Council in 2016 regarding the chosen leader stated QS. Al-Ma'idah verse 51 explicitly forbids making Jews and Christians as leaders and the proposition forbids making non-Muslims as leaders. And scholars are required to convey the contents of surah al-Ma'idah verse 51 as an obligation to choose Muslim leaders and believe in the truth of the contents of surah al-Ma'idah verse 51 as a guide in choosing leaders. That is because the MUI "monopolizes" the interpretation of Ø§ÙŽÙˆÙ’Ù„ÙÙŠÙŽØ§Ø¡ with "leaders" only. So prospective leaders who have met the criteria as leaders but are not Muslim then are not leaders who must be chosen.Keywords: abstentions fatwa; MUI version leader; Al-Ma'idah verse 51 MUI interpretation; Ahok Al-Maidah 51.Â ABSTRAKKeputusan Majelis Ulama Indonesia tahun 2009 sesuai dengan UU nomor 39 Tahun 1999 tentang HAM pasal 43 dan UU nomor 12 Tahun 2005 Tentang Pengesahan Kovenan Hak Sipil Politik pasal 25. Dalam hal ini MUI moderat. Keputusan Majelis Ulama Indonesia Tahun 2016 tentang pemimpin yangÂ  dipilihÂ  menyatakan QS. Al-Maâ€™idah ayat 51 secara eksplisit melarang menjadikan Yahudi dan Nasrani sebagai pemimpin dan dalil larangan menjadikan non Muslim sebagai pemimpin. Dan ulama wajib menyampaikan isi surah al-Maâ€™idah ayat 51sebagai wajibnya memilih pemimpin muslim dan meyakini kebenaran isi surah al-Maâ€™idah ayat 51 sebagai panduan dalam memilih pemimpin. Hal itu karena MUI â€˜memonopoliâ€™ tafsir Ø§ÙŽÙˆÙ’Ù„ÙÙŠÙŽØ§Ø¡Â  dengan â€œpemimpin-pemimpinâ€ saja. Jadi calon pemimpin yang telah memenuhi kriteria sebagai pemimpin namun tidak beragama Islam maka bukanlah pemimpin yang harus dipilih. Kata kunci: fatwa golput; Â pemimpin versi MUI; tafsir Al-Maâ€™idah ayat 51 MUI; Ahok Al-Maidah 51.